Imbalance‐based primary frequency control for converter‐fed microgrid. Issue 2 (15th June 2021) - Suh, Jaewan; Lee, Jaehyeong; Jung, Seungmin; Yoon, Minhan
Abstract: Frequency droop control is a simple and effective frequency control method. However, it is not appropriate as a primary frequency control for microgrids with energy storage systems and voltage source converters (VSCs) owing to their slow response speed. In addition, it is difficult to determine the grid balance only with frequency deviation. In this paper, a new converter‐fed microgrid primary frequency control method based on the estimated active power imbalance for fast response and less variability in the transmission system is proposed. The active power imbalance is estimated via frequency deviation, frequency drop speed and the modified swing equation. The estimated imbalance indicates the status of the power imbalance more quickly and accurately than the frequency deviation. The proposed method does not require communication devices, responds quickly to frequency drops, and prevents unnecessary operation of the grid‐connected VSC because it uses the estimated imbalance instead of the frequency or angle for droop control. Simulation results show that the proposed method is significantly faster than frequency droop control methods, improves the rate of change of frequency and frequency nadir and reduces variability in the transmission system.